Elektroniska underskrifter - En studie om den svenska regleringen med särskilt fokus på köp av fast egendom - Champari,Amir (2020)
The purpose of this study is to investigate what the current regulation of electronic signatures in Sweden is and whether the formal requirements for property purchases can be considered met when using electronic signatures. The conclusion is that the eIDAS-regulation and supplementary law (2016:561) with provisions to the EU-regulation on electronic identification regulate electronic signatures in Sweden. Electronic signatures makes it easier for agreements to come to fruition, from small, simple purchases to larger, more unusual purchases. The eIDAS-regulation is an initiative from the EU to promote clarity and uniform regulation for the Member States' various electronic ID-systems and trusted services. The form requirement “signature” according to Chapter 4 section 1 paragraph 1 (4 kap. 1 § 1 st.) JB makes it impossible for parties in the future to sign property transfers via electronic signatures. If a change in the law or an addition in the form requirement according to Chapter 4. Section 1 paragraph 1 JB would happen, the legislature should consider whether society is ready to do such a big deal via electronic media.
Keywords: Elektroniska underskrifter; digital signatures; formkrav; fastighetsköp; Jordabalken; eIDAS; PKI